2DFQ: Two-Dimensional Fair Queuing for Multi-Tenant Cloud Services - Mace, Jonathan; Bodík, Peter; Musuvathi, Madan; Fonseca, Rodrigo; Varadarajan, Krishnan (SIGCOMM 2016, 2016)
In many important cloud services, different tenants execute their requests in the thread pool of the same process, requiring fair sharing of resources. However, using fair queue schedulers to provide fairness in this context is difficult because of high execution concurrency, and because request costs are unknown and have high variance. Using fair schedulers like WFQ and WF2Q in such settings leads to bursty schedules, where large requests block small ones for long periods of time. In this paper, we propose Two-Dimensional Fair Queuing (2DFQ), which spreads requests of different costs across different threads and minimizes the impact of tenants with unpredictable requests. In evaluation on production workloads from Azure Storage, a large-scale cloud system at Microsoft, we show that 2DFQ reduces the burstiness of service by 1-2 orders of magnitude. On workloads where many large requests compete with small ones, 2DFQ improves 99th percentile latencies by up to 2 orders of magnitude.